Deep Eutectic Solvents for Boosting Electrochemical Energy Storage and Conversion: A Review and Perspective. (11th March 2021) - Wu, Junxiong; Liang, Qinghua; Yu, Xiaoliang; Lü, Qiu‐Feng; Ma, Lianbo; Qin, Xianying; Chen, Guohua; Li, Baohua
Abstract: The pursuit of sustainable energy utilization arouses increasing interest in efficiently producing durable battery materials and catalysts with minimum environmental impact. As green, safe, and cheap eutectic mixtures, deep eutectic solvents (DESs) provide tremendous opportunities and open up attractive perspectives as charge transfer and reaction media for electrochemical energy storage and conversion (EESC). In this review, the fundamental properties of DESs are first summarized. Then, the important roles that DESs play in various EESC technologies including advanced electrolytes for batteries/supercapacitors, media for the preparation of electrode materials and catalysts, and extracting agents for battery recycling are systematically reviewed. A particular focus is placed on the fundamental understanding of structure–composition–property–performance relationships. Finally, the challenges for the controllable design of DESs for EESC applications and future developments are presented. This review is expected to shed light on developing advanced DESs for next‐generation EESC systems. Abstract : This review presents recent advances in deep eutectic solvents (DESs) for electrochemical energy storage and conversion (EESC) technologies, including advanced electrolytes for batteries/supercapacitors, media for the preparation of electrode materials and catalysts, and extracting agents for battery recycling. The challenges and future research directions for DESs in EESC applications are also outlined.